Ενότητα 2 / Ενότητα 2 - Γιωβανίτσα Πηνελόπη (ΑΡΙΣΤΟΤΕΛΕΙΟ ΠΑΝΕΠΙΣΤΗΜΙΟ ΘΕΣΣΑΛΟΝΙΚΗΣ, 2016)
Ενότητα 2: Υπότιτλοι AUTHORWAVE When we're together I'm in a dream world Of sweet delight Many times I whisper A mano mio It was just a phrase That I heard in play I was acting a part But now when I whisper A mano mio Can't you tell I care By the feeling there Cause it comes from my heart I want you ever I love my darling Wanting to hold you And hold you tight A mano mio Love me forever And let forever Love begin tonight Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE When we're together Many times I whisper A mano mio It was just a phrase That I heard in play I was acting a part But now when I whisper A mano mio Can't you tell I care By the feeling there Cause it comes from my heart I want you ever I love my darling Wanting to hold you And hold you tight A mano mio Love me forever And let forever Begin tonight And let forever Begin tonight And let forever Begin tonight